Municipal regulation of residential landscapes across US cities: Patterns and implications for landscape sustainability. (1st December 2020) - Larson, Kelli L.; Andrade, Riley; Nelson, Kristen C.; Wheeler, Megan M.; Engebreston, Jesse M.; Hall, Sharon J.; Avolio, Meghan L.; Groffman, Peter M.; Grove, Morgan; Heffernan, James B.; Hobbie, Sarah E.; Lerman, Susannah B.; et al.
Abstract: Local regulations on residential landscapes (yards and gardens) can facilitate or constrain ecosystem services and disservices in cities. To our knowledge, no studies have undertaken a comprehensive look at how municipalities regulate residential landscapes to achieve particular goals and to control management practices. Across six U.S. cities, we analyzed 156 municipal ordinances to examine regional patterns in local landscape regulations and their implications for sustainability. Specifically, we conducted content analysis to capture regulations aimed at: 1) goals pertaining to conservation and environmental management, aesthetics and nuisance avoidance, and health and wellbeing, and 2) management actions including vegetation maintenance, water and waste management, food production, and chemical inputs. Our results reveal significant variation in local and regional regulations. While regulatory goals stress stormwater management and nuisance avoidance, relatively few municipalities explicitly regulate residential yards to maintain property values, mitigate heat, or avoid allergens. Meanwhile, biological conservation and water quality protection are common goals, yet regulations on yard management practices (e.g., non-native plants or chemical inputs) sometimes contradict these purposes. In addition, regulations emphasizing aesthetics and the maintenance of vegetation, mowing of grass and weeds, as well as the removal of dead wood, may inhibit wildlife-friendly yards. As a whole, landscaping ordinances largely ignore tradeoffs between interacting goals and outcomes, thereby limiting their potential to support landscape sustainability. Recommendations therefore include coordinated, multiobjective planning through partnerships among planners, developers, researchers, and non-government entities at multiple scales. Highlights: Multi-objective planning and landscape design are key to sustainability. Municipal regulations on residential landscapes vary across six cities in the U.S. Regulations partially reflect regional climate conditions. Local landscape regulations may constrain wildlife-friendly yards. Regulations sometimes contradict each other and overlook tradeoffs.